(untitled) (Journal of Hama University, 2022)
The aim of the research is to investigate the degree to which third-grade teachers practice number sense skills in teaching mathematics, and to identify the differences in their views on the degree of their practice of these skills according to the two variables (years of experience and training courses), to achieve the objectives of the research, the descriptive analytical approach was used, which was designed A questionnaire consisting of (34) items, distributed on two axes (implementation and evaluation), and was applied during the second semester of the 2021-2022 school year. A sample of (150) male and female teachers were filled out in the schools of the first cycle of basic education in the city of Hama. The results of the study showed:- The degree to which the third grade teachers practice number sense skills in teaching mathematics came at a high rate. There are statistically significant differences attributable to the variable number of years of experience from the teachers’ point of view about the degree to which they practice numerical sense skills, in favor of the longer number of years of experience. There are statistically significant differences attributable to the variable of training courses about the degree to which teachers practice number sense skills in favor of teachers who have followed one or more educational courses.